"Doing Conscience Over": The Reformulation of the Doctrine of Conscience in the Theological Ethics of Karl Barth and Paul Lehmann - Ziegler, Philip G. (Toronto journal of theology, 1998)
Thanks to the posthumous publication of the ethics lectures which Karl Barth delivered in Munster in 1928-1929 and then again in Bonn in 1930-1931, the contemporary reader is offered a glimpse both of things that were to come as well as of things which were never to come. 1 These lectures anticipate, both formally and materially, much of what would later appear in the substantive ethical sections of the four volumes of Barth's Church Dogmatics published over the subsequent decades. But of particular interest for the student of Barth's theology, these lectures in fact go farther than the ethical program of the Dogmatics would ultimately reach, offering an account of the "ethics of redemption" (i.e., ethics from the perspective of eschatology), which would have formed the final sections of the unwritten fifth volume. It is this latter material, the ethics of redemption and more specifically the account of conscience which constitutes an important element within it, which will be the particular the focus of our inquiry.